Quota Formula Review : Data Update and Further Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
In March 2012, the Executive Board held its first formal discussion on the comprehensive review of the quota formula. This review, to be completed by January 2013, is an important part of the quota and governance reforms agreed in 2010. Directors stressed the importance of agreeing on a quota formula that better reflects members' relative positions in the global economy for future discussions on the 15th General Review of Quotas. This view was reiterated in April by the IMFC, which looked forward to an agreement by January 2013: " ... on a simple and transparent quota formula that better reflects members' relative positions in the world economy." The IMFC also reaffirmed its commitment to complete the 15th quota review by January 2014. It noted that any realignment is expected to result in increases in the quota shares of dynamic economies in line with their relative positions in the world economy, and hence likely in the share of EMDCs as a whole; and that steps shall be taken to protect the voice and representation of the poorest members. The Board held an informal follow-up meeting on June 13, 2012.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet